2018
DOI: 10.1186/s12943-018-0770-8
|View full text |Cite
|
Sign up to set email alerts
|

A coordinate deregulation of microRNAs expressed in mucosa adjacent to tumor predicts relapse after resection in localized colon cancer

Abstract: Up to 20% of colorectal cancer (CRC) node-negative patients develop loco-regional or distant recurrences within 5 years from surgery. No predictive biomarker able to identify the node-negative subjects at high risk of relapse after curative treatment is presently available.Forty-eight localized (i.e. stage I-II) colon cancer patients who underwent radical tumor resection were considered. The expression of five miRNAs, involved in CRC progression, was investigated by qRT-PCR in both tumor tissue and matched nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…In particular, the NABP1 gene, which is involved in the GO “DNA repair” pathway taking part in the apoptotic process, was significantly enriched in the anti-miR-182-treated tumorigenic cell line. Interestingly, a significant NABP1 expression decrease was observed in a pool of primary CRC samples, in which increased miR-182 levels were previously assessed [21], compared to matched normal colon mucosa (Fig. 4c).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…In particular, the NABP1 gene, which is involved in the GO “DNA repair” pathway taking part in the apoptotic process, was significantly enriched in the anti-miR-182-treated tumorigenic cell line. Interestingly, a significant NABP1 expression decrease was observed in a pool of primary CRC samples, in which increased miR-182 levels were previously assessed [21], compared to matched normal colon mucosa (Fig. 4c).…”
Section: Resultsmentioning
confidence: 61%
“…This seems to indicate that the miR-182 upregulation occurs in early premalignant development and is associated with the maintenance of the malignant phenotype [19]. Furthermore, we also demonstrated that high expression levels of miR-182 do not characterize mucosa samples from patients with inflammatory bowel disease, thus suggesting that its deregulation is not a mere consequence of the chronic inflammatory process [21]. Interestingly, in a large functional miRNA screening, Cekaite et al found that miR-182 gene, a component of miRNA cluster miR-183-96-182 located in 7q32 genomic region, is amplified in 26% of primary CRC and 30% of liver metastases [25].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, miRNAs from tumour-adjacent mucosa have been studied for the prediction of relapse risk after curative treatment. Four miRNAs (miR-18a, miR-21, miR-182 and miR-183) were found with coordinate deregulation in the normal mucosa adjacent to the tumour, which is predictive of relapse within 55 months from curative surgery in 48 localized CRC patients who underwent radical tumour resection [66].…”
Section: Mirnas For Crc Diagnosis Treatment and Recurrence Predictionmentioning
confidence: 99%
“…Despite the enormous potential of immunotherapy, not all patients or all tumors respond in the same manner to treatment. There are still difficulties to know the best way to select patients that will greatly benefit from this type of therapy, and the only biomarker with clinical utility for immunotherapy, such the expression of PD-L1, which has been studied in many clinical trials [ 6 , 7 , 8 ], is not completely accurate and presents several limitations [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%